Allelopathic effects of Antarctic lichen and mosses on the growth of algae (extended abstract) - Akiyama, Masaru; Kanda, Hiroshi; Ohtani, Shuji (National Institute of Polar Research, 1989)
P(論文) departmental bulletin paper